Heterologous Expression of a Ferritin Homologue Gene PpFer1 from Prunus persica Enhances Plant Tolerance to Iron Toxicity and H2O2 Stress in Arabidopsis thaliana - Yong Yang; Jinjin Zhang; Mengyuan Li; Youzheng Ning; Yifei Tao; Shengpeng Shi; Adeeba Dark; Zhizhong Song (Plants, 2023)
In plants, ferritin proteins play an important role in iron (Fe) storage which contributes to plant growth and development. However, the biological functions of ferritins in fruit trees are essentially unknown. In this study, three Ferritin genes were isolated from ‘Zhentong No. 3’ peach, which were named PpFer1-PpFer3. The expression levels of these genes were different in distinct tissues/organs. Notably, PpFer1 was the most abundantly expressed Ferritin family gene in all tested tissues of ‘Zhentong No. 3’ peach; its expression levels were significantly enhanced throughout the entire peach seedling under Fe toxicity and H2O2 stress, particularly in the leaves. In addition, over-expression of PpFer1 was effective in rescuing the retarded growth of Arabidopsis fer1-2 knockout mutant, embodied in enhanced fresh weight, primary root length, lateral root numbers, total root length, total leaf chlorophyll, stomatal conductance (Gs), net photosynthetic rate (Pn), transpiration rate, and tissue Fe concentration. This study provides insights into understanding the molecular mechanisms of Fe storage and sequestration in perennial fruit trees.